COMPARISON ANALYSIS OF INDEX IDX30 OPTIMAL SHARE PORTFOLIO WITH INDONESIAN EQUITY FUND PORTFOLIO PERFORMANCE - Yoko Mashonia Panjaitan; Nisrul Irawati; Isfenti Sadalia (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Based on the results of the study, the conclusions that can be drawn are as follows. The optimal portfolio calculation results on the Single Index Model method for stocks show that stocks with UNVR issuers are the only ones that are optimal. Whereas in Mutual Funds there is no optimal portfolio calculation results. The results of calculations using the Markowitz method for all stock issuers obtained a return value of 0.000634 with a risk of 0.036057, namely at alpha 0.9. Meanwhile, for all stock mutual fund issuers, a return value of 0.003195 was obtained with a risk of 0.033629, namely at alpha 0.9. Compared to calculations using the Single Index Model Method for all stocks, a return value of 0.0050 is obtained with a risk of 0.0218, while for Equity Mutual Fund issuers a return value of 0.0072 is obtained with a risk of 0.0194, in this case the calculation of the optimal portfolio in stocks and mutual funds using the Markowitz Method produces a smaller return and greater risk than the Single Index Model method. The Single Index Model method which produces stock return calculations is superior to the Markowitz method. This is obtained from the results of the return value obtained on the Single Index Model which is greater than the Markowitz model so that stock investment will be more profitable if using the Single Index Model method. The Single Index Model method is superior to the Markowitz method in calculating mutual fund returns. This is obtained from the results of the return value obtained in the Single Index Model which is greater than the Markowitz model so that mutual fund investment will be more profitable if using the Single Index Model method. The Single Index Model method is superior to the Markowitz method in calculating stock risk. This is obtained from the results of the stock risk value obtained in the Single Index Model which is smaller than the Markowitz model so that stock investment will be riskier if using the Markowitz method. The Single Index Model method is superior to the Markowitz method in calculating mutual fund risk. This is obtained from the results of the mutual fund risk values obtained in the Single Index Model which are smaller than the Markowitz model so that mutual fund investments will be riskier if using the Markowitz method.